A Descriptive Study On Teaching Writing To The First Year Students Of MTs Salafiyah Kajen Margoyoso Pati - Nailu Rohmah, Ana (2012)
This research paper is intended to describe a teaching writing to the first year students of MTS Salafiyah Kajen Margoyoso Pati. The writer focuses the teaching-learning process of writing, on the first year student. The objective of this research are 1) to describe technique implemented in teaching writing, 2) kinds of difficulties faced in learning writing, and 3) kinds of strategies used by teacher to solve the student's difficulties. The type of this research is descriptive research which does not include any calculation or statistic procedure. The object of this research is teaching writing. The subjects of this research are English teacher and students. The data are taken from informant, events, and document. The techniques of collecting data are observation, employing interview, and analyzing document. The setting of this research is MTs Salafiyah Kajen Margoyoso Pati. MTs Salafiyah is one of state school in Pati district. The addres is on Kajen Margoyoso Pati Central Java. It has post code 59154. It is opened in January 1, 1933 by K.H.Baedlowi Sirodj. There are 15 teachers. Two teachers of those amounts are English teacher. The writer was took MTs Salafiyah as object of this research caused the students of MTs Salafiyah has some problem faced in writing skill, especially in writing paragraph. The study shows that 1) Technique implemented in teaching learning process of writing to the first year students are game and contextual learning. 2) The kinds of difficulties faced in learning writing by the first students are vocabulary, tenses, and expressing idea in writing. 3) The kinds of strategies used by teacher to solve student's difficulties are giving example of text and giving instruction